Conflict resolution using statistical approach - Omwenga, Vincent O.; Mwita, Peter N. (Academic Journals, 2010)
Conflict can be described as a condition in which actions of one person prevent or compel some outcome at the resistance of the other. Quite often this can be seen as “two or more competing, often incompatible, responses to same event”. In this paper, a statistical approach to conflict resolution using the concept of bargaining game theory is presented. The approach gives chances of failure that are minimal since any offer made in a conflict situation is tied to the likelihood of it being accepted as it takes into considerations the demands from the other party. The approach presents a fair way of solving a conflict without affecting a system. An employer-employee relationship was used to illustrate the application of the approach.
Keywords: Bargaining game theory; Conflict; Ultimatum game